2010
DOI: 10.2174/1874312901004010015
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Patient/Physician Satisfaction with Subcutaneously Administered Methotrexate Provided in Two Formulations of Different Drug Concentrations in Patients with Rheumatoid Arthritis~!2010-01-14~!2010-02-08~!2010-03-18~!

Abstract: Objectives:To determine preference, satisfaction, usability and local tolerability by patients, physicians and study nurses of two subcutaneously administered methotrexate (MTX) formulations of different concentrations.Methods:This was an open-label, comparative, within-patient controlled, multicentre study of 132 patients with rheumatoid arthritis (RA). MTX treatment consisted of 20 mg/week administered as a medium-concentration formulation (MC) (2.0 ml of 10 mg/ml solution in prefilled syringe; separate need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 8 publications
3
22
0
1
Order By: Relevance
“…MTX was compared in several clinical trials. The outcome suggested that the s.c. route is superior regarding clinical efficacy, tolerability and AUC or drug levels when ≥15 mg MTX is applied …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTX was compared in several clinical trials. The outcome suggested that the s.c. route is superior regarding clinical efficacy, tolerability and AUC or drug levels when ≥15 mg MTX is applied …”
Section: Discussionmentioning
confidence: 99%
“…The outcome suggested that the s.c. route is superior regarding clinical efficacy, tolerability and AUC or drug levels when ≥15 mg MTX is applied. 3,29,30 A metaanalysis recommended the most efficient therapy starting with an oral dose of 15 mg/week, to increase in 5 mg steps to 30 mg as a maximum dose and/or to switch to the subcutaneous application when therapy fails. 2 Since the bioavailability of MTX in psoriasis plaques was higher in all patients compared to the unaffected skin and also reached significantly higher drug levels the practical aspect consequence is that it might be better to start with a lower dose of MTX such as 5 or 7.5 mg per week and then wait longer until the full efficacy for the treatment of psoriasis is reached rather than increasing the dose too early given the huge individual differences in MTX metabolism based on a different pharmacogenetic background 4,26,27,31 preventing unnecessary toxicity for patients' unaffected skin or mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Greater familiarity with subcutaneous injections among dermatology patients will undoubtedly contribute to this increased use, as will the introduction of higher-concentration formulations (50 mg/mL) in prefilled syringes, as these offer greater tolerability and convenience 53 and are preferred to the 10-mg/mL formulations by the majority of patients treated with 20 mg per week. 54 Single-dose formulations also have environmental and safety benefits as they eliminate the need to handle and discard unused portions of vials or syringes. 55…”
Section: Patterns Of Use and Administration Routesmentioning
confidence: 99%
“…Two MTX formulations for SC use were tested in an open-label, comparative, within-patient controlled, multicenter study in 132 patients with RA [Müller-Ladner et al 2010]. MTX treatment consisted of 20 mg/week administered as a medium-concentration formulation (2.0 ml of 10 mg/ml solution in prefilled syringe; separate needle) which was compared to a novel high-concentration formulation (0.4 ml of 50 mg/ml in prefilled syringe; pre-attached needle).…”
Section: Introductionmentioning
confidence: 99%